2022
DOI: 10.3390/ijms231911130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RAGE Deletion on the Cardiac Transcriptome during Aging

Abstract: Cardiac aging is characterized by increased cardiomyocyte hypertrophy, myocardial stiffness, and fibrosis, which enhance cardiovascular risk. The receptor for advanced glycation end-products (RAGE) is involved in several age-related diseases. RAGE knockout (Rage−/−) mice show an acceleration of cardiac dimension changes and interstitial fibrosis with aging. This study identifies the age-associated cardiac gene expression signature induced by RAGE deletion. We analyzed the left ventricle transcriptome of 2.5-(Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…AGE/RAGE signaling increases OS leading to diabetes mediated vascular calcification. 112 Previous research linked the AGE/RAGE pathway to CD, 113 CVD, 114 and VCI. 115 The link between the Notch pathway to CD, 116 CVD, 117 and VCI 118 are also recognized.…”
Section: Potential Implications Of the Identified Pathwaysmentioning
confidence: 99%
“…AGE/RAGE signaling increases OS leading to diabetes mediated vascular calcification. 112 Previous research linked the AGE/RAGE pathway to CD, 113 CVD, 114 and VCI. 115 The link between the Notch pathway to CD, 116 CVD, 117 and VCI 118 are also recognized.…”
Section: Potential Implications Of the Identified Pathwaysmentioning
confidence: 99%
“…When changes in differentially expressed genes (DEGs) were mapped onto the Kyoto Encyclopedia of Genes and Genomes (KEGG) database, the AGE-RAGE signalling pathway in diabetic complications emerged among the pathways that had the most critical implications in the process of development of atherosclerotic plaques in fibroblast populations. Furthermore, in the study to identify the age-associated cardiac gene expression signature induced by RAGE deletion, functional inference analysis of transcriptome in the left ventricle of RageÀ/À and WT mice revealed that RAGE deletion is associated with alterations in the expression of genes related to cardiac remodelling, adaptive immunity, T-cell differentiation and activation, IFN signalling and stress pathways (Scavello et al, 2022).…”
Section: Ragementioning
confidence: 99%